Investigation on high-temperature resistance to permanent deformation of waste leather modified asphalt. (3rd May 2021) - Lv, Songtao; Guo, Yanpeng; Xia, Chengdong; Liu, Chaochao; Hu, Long; Guo, Shuaicheng; Wang, Xiaofeng; Borges Cabrera, Milkos; Li, Mi
Highlights: The waste leather can enhance the rotational viscosity of the asphalt binder. The addition of waste leather powder can enhance the high-temperature properties. The modification with the waste leather is mainly a physical process. Abstract: This study analyzed the feasibility of modifying the asphalt binder with the waste leather (WL). The 70# base asphalt was selected as the base matrix and four samples with different waste leather content were prepared. The test results indicated that the rotational viscosity of the waste leather modified asphalt was obviously higher than that of the original binder. Furthermore, it is found that the added waste leather increases the elastic component of the asphalt through the dynamic shear rheometer (DSR) test, thus enhances the high-temperature rheological properties and creep recovery ability of the asphalt. The modification with waste leather can also enhance the anti-aging properties of the asphalt and the enhancement effect generally increases with the leather content. The fourier transform infrared spectroscopy (FTIR), results indicate the modification with the waste leather is mainly a physical process without changing the chemical structure of the asphalt binder. This study pcreates new recycling routes for the waste leather and provides a considerable reference for the application of the waste leather modified asphalt binder.